Voluntary Environmental Disclosure by Australian Listed Mineral Mining Companies: An Application of Stakeholder Theory - Christopher, Theo; Hutomo, Sigit; Monroe, Gary (The International Journal of Accounting and Business Society, 1997)
Within the stakeholder theory framework this paper examines the extent of voluntary environmental disclosure (ED) in relation to characteristics of Australian listed mineral mining ï¬rms. Three indexes, words, unweighted and weighted index, are calculated to measure the association of total ED and categories of total ED with ï¬rm characteristics within the three dimensions of stockholder theory. We ï¬nd that the three indexes for total ED and categories of disclosure are signiï¬cantly associated. Consequently, a single construct is employed as a surrogate for the indexes. The result of Ordinary Least Squares Regression of this construct as a dependent variable with ownership diffusion, ï¬nancial leverage and membership of the Australian Mining Industry Council (AMIC) as proxies for stakeholder power; the presence of a corporate environmental committee as a proxy for strategic posture; retum on equity and systematic risk as proxies for economic performance ; and ï¬rm size and commercial production as control variables showed that membership of AMIC and size were statistically signiï¬cant. The implication of this ï¬nding is that ï¬nancial variables do not explain voluntary ED and that the variables used in the strategic posture and economic performance dimensions of stakeholder theory are not signiï¬cant. This implies, subject to limitations of the study, that the regulators of accounting infonnation will need to issue an accounting standard if they